Fatal opiates overdose. Toxicological identification of various metabolites in a blood sample by GC-MS after silylation - Balíková, M; Maresová, V (Forensic science international, 1998)
A fatal opiates overdose, where ethylmorphine, hydrocodone, dihydrocodeine and codeine were consumed concomitantly, is reported. This case report may contribute to data on fatal blood concentrations of drugs with rare incidence. The relative retention times in capillary gas chromatography and full mass spectra of various opiates in their silylated forms, detected together in one sample, may serve as a helpful analytical reference for clinical and forensic toxicologists.
Keywords: Opioid-Related Disorders; toxikologie; Toxicology; kodein; mužské pohlaví; poruchy spojené s užíváním opiátů; Drug Overdose; Adult; Fatal Outcome; hydrokodon; ethylmorfin; Humans; plynová chromatografie s hmotnostně spektrometrickou detekcí; Codeine; dospělí; předávkování léky; Ethylmorphine; Hydrocodone; Gas Chromatography-Mass Spectrometry; fatální výsledek; lidé; Male